Reproductive Endocrinology and Infertility Integrating Modern Clinical and Laboratory Practice - Carrell, Douglas T.; Peterson, C. Matthew; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Management of the modern reproductive endocrinology and infertility clinic has become very complex. In addition to the medical and scientific aspects, it is crucial that the modern director be aware of of incongruent fields such as marketing, accounting, management, and regulatory issues. Reproductive Endocrinology and Infertility: Integrating Modern Clinical and Laboratory Practice was developed to assist the practicing reproductive endocrinologist and/or laboratory director by providing an overview of relevant scientific, medical, and management issues in a single volume. Experts in all pertinent areas present concise, practical, evidence-based summaries of relevant topics, producing a key resource for physicians and scientists engaged in this exciting field of medicine. As novel technologies continue to amplify, Reproductive Endocrinology and Infertility: Integrating Modern Clinical and Laboratory Practice offers insight into development, and imparts extra confidence to practitioners in handling the many demands presented by their work.
Management of the R.E.I. Clinic and Laboratories -- Characteristics of a Successful R.E.I. Clinic and Laboratory -- Assisted Reproductive Technology Practice Management -- Collaboration Within the Reproductive Endocrinology and Infertility Practice: Integration of Laboratory and Clinic Operations -- Informed Consent in Advanced Reproductive Technology -- Reproductive Laboratory Regulations, Certifications and Reporting Systems -- Successfully Integrating the FDA Regulations into Your Practice -- Psychosocial Consequences of Infertility and Treatment -- A Live Baby or Your Money Back: The Marketing of In Vitro Fertilization Procedures -- Female Reproductive Physiology and Medicine -- Ovulation: A Molecular View -- Clinical Evaluation of Female Factor Infertility -- Polycystic Ovary Syndrome -- The Current Status for Metformin Use in Reproductive Medicine -- Clinical Aspects of Endometriosis -- Common Endocrinopathies in Reproductive Endocrinology -- Acquired Uterine Factors and Infertility -- Müllerian (Paramesonephric) Anomalies and Associated Wolffian (Mesonephric) Duct Malformations -- Recurrent Miscarriage -- Laparoscopy in the Diagnosis and Treatment of Female Infertility -- Turner Syndrome -- Errors in Chromosome Segregation During Oogenesis and Early Embryogenesis -- Male Reproductive Physiology and Medicine -- An Overview of Sperm Production -- Meiotic Recombination and Errors During Spermatogenesis -- Clinical Evaluation and Treatment of Male Factor Infertility -- Semen Analysis: Essentials for the Clinician -- Sperm Capacitation, the Acrosome Reaction, and Fertilization -- Advanced Tests of Sperm Function -- Genetic Testing of Male Infertility -- Varicocele and Male Infertility -- Sperm Retrieval Techniques -- The Clinical Utility of the Evaluation of Sperm Chromatin -- Assisted Reproductive Therapies: Artificial Insemination -- Artificial Insemination: Intrauterine Insemination -- Sperm Preparation for Artificial Insemination -- Sperm Banking, Donation, and Transport in the Age of Assisted Reproduction: Federal and State Regulation -- Reproductive Treatment of HIV-1 Discordant Couples -- Ovulation Induction -- Transvaginal Sonography in Reproductive Endocrinology and Infertility -- Assisted Reproductive Therapy: In Vitro Fertilization -- Establishing the IVF Laboratory: A Systems View -- Preparation and Selection of Sperm for IVF and ICSI -- The Genetic and Epigenetic Contributions of Sperm to Early Embryogenesis -- Micromanipulation of Human Oocytes and Embryos: Applications of Intracytoplasmic Sperm Injection and Assisted Hatching in Infertility Treatment -- Embryo Culture Techniques -- In-vitro Maturation of Human Oocytes -- Integrating Preimplantation Genetic Diagnosis into the ART Laboratory -- Evaluation and Selection of Preimplantation Embryos for Transfer -- Embryo Transfer in IVF: Evidence-Based Clinical Practice -- Cryopreservation of Human Oocytes and Embryos -- Preserving Fertility -- Ovarian Hyperstimulation Syndrome -- Pregnancy Outcomes in Infertile Couples -- The Impact of Complementary Medicine on In Vitro Fertilization -- Research in the REI Practice and Laboratories -- Designing a Clinical Research Infrastructure -- Integrating Research into a Clinical Practice -- Research Regulations: The Role of the Institutional Review Board -- Technology Transfer and Its Role in the Practice of Reproductive Endocrinology and Infertility -- The Environment and Reproduction: Endocrine Disruption, Reproductive Impairment, and Epigenetics.
Keywords: Medicine; Gynecology; Endocrinology; Reproductive Medicine; Urology; Medicine & Public Health; Endocrinology; Reproductive Medicine; Urology/Andrology.; Gynecology